Nelson Jen An Chao Oral History Interview, 2021 - Duke University. Medical Center. Department of Medicine. (2021)
This oral history interview was conducted with Dr. Nelson Jen An Chao on March 25, 2021 by Joseph O'Connell as part of the Department of Medicine's Oral History Project. During the interview, Chao discusses his upbringing in Brazil, his reflections on his medical training, his observations on transplant as a complex medical issue, and a description of his work leading the Duke Global Cancer Program. The themes of these interviews include leadership, equity in medicine, cancer treatment, and stem cell transplantation.